NETosis in Wound Healing: When Enough Is Enough - Maurizio Sabbatini; Valeria Magnelli; Filippo Renò (Cells, 2021)
The neutrophils extracellular traps (NETs) are a meshwork of chromatin, histonic and non-histonic proteins, and microbicidal agents spread outside the cell by a series of nuclear and cytoplasmic events, collectively called NETosis. NETosis, initially only considered a defensive/apoptotic mechanism, is now considered an extreme defensive solution, which in particular situations induces strong negative effects on tissue physiology, causing or exacerbating pathologies as recently shown in NETs-mediated organ damage in COVID-19 patients. The positive effects of NETs on wound healing have been linked to their antimicrobial activity, while the negative effects appear to be more common in a plethora of pathological conditions (such as diabetes) and linked to a NETosis upregulation. Recent evidence suggests there are other positive physiological NETs effects on wound healing that are worthy of a broader research effort.